From Flood Control to Integrated Water Resource Management Lessons for the Gulf Coast from Flooding in Other Places in the Last Sixty Years - Kahan, James P. (RAND Corporation, 2006)
The loss of life and devastation in the Gulf coast region of the United States after the hurricane season of 2005 has led to considerable debate about how to recover from the damage and mitigate damage from future incidents. This document reports the experiences of four major floods since 1948 (two in the United States, one in the Netherlands, and one in China), to draw lessons for the Gulf coast restoration effort.